Unleashing Synergies: Interplay between Human Resource Management, Strategic Marketing, and Corporate Financial Performance - Guasmin; Rajindra, Rajindra (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This research explores the confluence of Human Resource Management (HRM), Strategic Marketing Management (SMM), and Corporate Financial Performance (CFP), offering a comprehensive understanding of their synergistic effects on organizational success. The study provides empirical evidence supporting the theory that a strategic blend of HRM and SMM is instrumental in enhancing financial performance. Efficient HRM practices, which improve productivity and innovation, coupled with effective SMM strategies that strengthen market positioning and revenue flows, are shown to be significant drivers of sustainable financial growth. The managerial implications of this integration are profound, underscoring the need for business leaders to consider investments in human resource development and strategic marketing as pivotal to the company's long-term success rather than as mere departmental functions. Through a quantitative analysis using SMARTPLS with a sample size of 150, the research contributes to management literature by highlighting the often-overlooked functional interconnections between HRM and SMM divisions. It challenges the conventional compartmentalization of these functions and advocates for a more integrative approach within corporate strategies. The findings indicate that companies embracing this integrated approach tend to report superior financial performance. This study addresses a gap in existing literature by demonstrating the collective impact of HRM and SMM on CFP across various industries, organization sizes, and cultural contexts, emphasizing the strategic amalgamation of these practices as a source of competitive advantage and financial enhancement.